Problem of Statelessness in Nepal - Upadhyay, Rameshwor (NUTA Journal, 2019)
This paper highlighted Nepalese statelessness issue from Nationality perspective. Nationality is one of the major human rights concerns of the citizens. In fact, citizenship is one of the major fundamental rights guaranteed by the constitution. According to the universal principle related to the statelessness, no one shall be arbitrarily deprived of his or her nationality. In this connection, on one hand, this paper traced out the international legal obligations created by the conventions to the state parties in which state must bear the responsibility for making national laws to comply with the international instruments. On the other hand, this paper also appraised statelessness related lacunae and shortcomings seen in Municipal laws as well as gender discriminatory laws that has been supporting citizens to become statelessness. By virtue being a one of the modern democratic states in the world, it is the responsibility of the government to protect and promote human rights of the citizens including women and children. Finally, this paper suggests government to take necessary initiation to change and repeal the discriminatory provisions related to citizenship which are seen in the constitution and other statutory laws.